Search for anomalous production of di-lepton events with missing transverse momentum in e+e- collisions at √S = 161 and 172 GeV - Ackerstaff,K; Alexander,G; Allison,J; Altekamp,N; Anderson,KJ; Anderson,S; Arcelli,S; Asai,S; Axen,D; Azuelos,G; Ball,AH; Barberio,E; et al. (European Physical Journal C, 1998)
Events containing two charged leptons and significant missing transverse momentum are selected from a data sample corresponding to a total integrated luminosity of 20.6 pb-1 at centre-of-mass energies of 161 GeV and 172 GeV. The observed number of events, four at 161 GeV and nine at 172 GeV, is consistent with the number expected from Standard Model processes, predominantly arising from W+W-1 production with each W decaying leptonically. This topology is also an experimental signature for the pair production of new particles that decay to a charged lepton accompanied by one or more invisible particles Further event selection criteria are described that optimise the sensitivity to particular new physics channels No evidence for new phenomena is observed and limits on the production of scalar charged lepton pairs and other new particles are presented.